Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Transport Findings 2019
DOI: 10.32866/8330
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the influence of commuters’ perception on the reliability ratio

Abstract: The dominant method for measuring values of travel time savings (VOT), and values of travel time reliability (VOR) is discrete choice modeling. Studies using revealed preference have tended to use travel times measured by devices such as loop detectors, and thus the perception error of travelers has been largely ignored. In this study, the influence of commuters’ perception error is investigated on data collected of commuters recruited from previous research. The subjects’ self-reported travel times from surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Transportation researchers may have control over the environment similar to psychological researchers through computer-based simulations and/or fixed-base vehicle simulators [1,2,6]. On the other hand, transportation researchers may collect data from field observations through questionnaires, cameras, GPS devices, and others [4,5,37,38]. It should be noted that there is an obvious trade-off between the analyst's control over the environment and the realism of the environment to the subjects.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Transportation researchers may have control over the environment similar to psychological researchers through computer-based simulations and/or fixed-base vehicle simulators [1,2,6]. On the other hand, transportation researchers may collect data from field observations through questionnaires, cameras, GPS devices, and others [4,5,37,38]. It should be noted that there is an obvious trade-off between the analyst's control over the environment and the realism of the environment to the subjects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reported travel time distributions were compared to the camera travel time distributions. Travel times for the same commute trips as reported by subjects from questionnaires and travel times as measured from GPS devices have been compared [38] . Both studies found that perception error was relevant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An interesting question that has received more attention recently is to what extent chosen routes deviate from the shortest time route, or how far is traffic from user equilibrium (Zhu and Levinson, 2012). Recent research confirms the hypothesis that models with self-reported travel times statistically fit the route choice data better in comparison to the models with measured travel times (Carrion and Levinson, 2013b). Perhaps the most challenging is to determine if time and non-time related attributes are consciously considered by the decision maker and therefore explicitly contribute to the utility, or if they influence route choice indirectly because they alter the travel time perception of the driver.…”
Section: Shortest Path Choicementioning
confidence: 85%
“…Abdel-Aty et al, 1997). Interestingly, in a recent study it was found that drivers value travel time variability more than travel time savings when analysing perceived travel times, while in contrast they value travel time savings more than travel time variability when actual travel times are analysed (Carrion and Levinson, 2013b). This finding highlights the relevance of considering measurements of perceived travel times in choice models.…”
Section: Choice Attributesmentioning
confidence: 95%
See 1 more Smart Citation